Influence of fracture orientation distribution function on the estimates of gas-hydrate saturation of site 10 at Krishna-Godavari Basin, India - Yudhvir Singh; Rajesh R. Nair (Annals of Geophysics, 2016)
We estimate the gas-hydrate saturation in fractured reservoirs of gas hydrate-rich marine sediments from Krishna-Godavari basin along the eastern margin of India. Effective medium modeling (EMM) is a combination of self-consistent approximation (SCA), differential effective medium (DEM) modeling and smoothing and it deals with the anisotropy associated with clay platelets’ orientation. It proves to be a good choice attributable to its dependency on physical parameters alone. Previous approaches appertain to the implementation of orientation distribution function (ODF) on clay platelets alone assuming a vertical ellipsoidal shape of gas hydrates whilst in the present study, we have implemented ODF on hydrate bearing fractures assigning an ellipsoidal shape to them as well. A bias of ~2-4% in the saturation estimates apparently streamlines the betterness of our method.